Efeito tripanocida da chalcona (2e,4e)-1-(2-hidroxi-3,4,6-trimetoxifenil)-5-fenilpenta-2,4-dien-1-ona em cepa Y de Trypanosoma cruzi - Ribeiro, Lyanna Rodrigues (2023)
Chagas disease (CD) is a common anthropozoonosis in Latin America, caused by the hemoflagellate protozoan agent Trypanosoma cruzi. It is a neglected infectious disease that represents a threat to areas considered non-endemic. The disease has acute and chronic clinical phases, with serious cardiac and gastrointestinal complications. There are only two drugs available for etiological treatment, Benznidazole (BZN) and Nifurtimox, which have adverse events, high discontinuation rates and are not very effective in therapy, making it necessary to search for new substances with trypanocidal activity. Chalcones are natural, synthetic or semisynthetic substances that have several biological properties, including trypanocidal activity. Therefore, they are promising for researching antichagasic activity. Therefore, the objective of the present work was to evaluate the trypanocidal activity of (2E,4E)-1-(2-hydroxy-3,4,6-trimethoxyphenyl)-5-phenylpenta- 2,4-dien-1-one (CPNC) and its mechanisms of action. For this, cytotoxicity in LLC-MK2 host cells was performed using the MTT reduction assay. From this, a concentration capable of inhibiting the growth of 50% of cells (CC50) was estimated. Then, epimastigotes and trypomastigotes were incubated with increasing concentrations of CPNC. The percentage of viable parasites was determined by counting in a Neubauer chamber. Guideline values were used to calculate the concentration capable of inhibiting 50% control of epimastigotes (IC50) and the concentration capable of killing 50% of trypomastigotes (LC50). The selectivity index (SI) was calculated by the ratio CC50/LC50. The anti-mastigote effect was evaluated in LLC-MK2-infected cells by determining the percentage of infected cells and the number of amastigotes within 100 cells. The mechanisms of cell death were investigated regarding the percentage of necrotic and apoptotic cells by labeling with 7-AAD and annexin V-PE, the cytoplasmic production of reactive oxygen species (ROS) by DCFH2-DA, and the change in mitochondrial transmembrane potential ( ΔΨm ) by rhodamine 123 (Rho123). Finally, molecular docking simulations were performed to evaluate the theoretical interaction of CPNC with the enzymes trypanothione reductase and cruzin. CPNC caused a cytotoxic effect on host cells at concentrations between 62.5 and 1000 μM, with CC50 = 355.5 ± 45.9 μM. Furthermore, it was able to inhibit the protection of epimastigotes at all concentrations tested in the three times, with IC50/24h = 39.9 ± 4.2 μM; IC50/48h = 48.5 ± 3.7 μM; and IC50/72h = 37.8 ± 3.5 μM. In trypomastigote forms, it was effective at all concentrations, with LC50 = 48.3 ± 13.4 μM, obtaining IS = 7.36. As for the anti- mastigote effect, there was a decrease in the number of infected cells and the number of amastigotes/100 cells. Flow cytometry assays showed that CPNC treatment caused loss of membrane integrity, ROS production, and a reduction in ΔΨm. In molecular docking tests, it was observed that CPNC interacted with regions of the catalytic sites of the two enzymes tested, which may help in understanding the mechanisms of action of the molecule on Trypanosoma cruzi. In conclusion, CPNC showed an antiparasitic effect on T. cruzi, which is promising for the development of new antichagasic drugs.